2015
DOI: 10.1016/j.amjmed.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Knee Osteoarthritis in Overweight Females: The First Preventive Randomized Controlled Trial in Osteoarthritis

Abstract: No significant main effects of the diet-and-exercise program and of glucosamine sulfate were found on incident knee osteoarthritis. Nevertheless, this trial provides valuable insights for future trial design for preventive osteoarthritis studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 25 publications
(13 reference statements)
1
82
1
Order By: Relevance
“…The PROOF study used a combined outcome measure of radiographic and clinical knee OA features in order to make a preventive randomized trial with a relatively short followup time feasible (26). In the non-weight loss group, 6% of all knees had incident radiographic knee OA (K/L $2) over the followup period.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The PROOF study used a combined outcome measure of radiographic and clinical knee OA features in order to make a preventive randomized trial with a relatively short followup time feasible (26). In the non-weight loss group, 6% of all knees had incident radiographic knee OA (K/L $2) over the followup period.…”
Section: Discussionmentioning
confidence: 99%
“…A full description of the study protocol can be found elsewhere (26). In short, this 2.5-year followup study aimed to evaluate the preventive effect of a diet and exercise program and oral glucosamine sulfate (double-blind, placebo-controlled) on the onset of knee OA in a 2 3 2 factorial design.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations